Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan di PT Pelindo Multi Terminal Belawan - Regina Felisita Goretta Napitu; John Sihar Manurung; Anggiat Parlindungan; Dewi Comala Sari (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the influence of work environment and work motivation on employee performance at PT Pelindo Multi Terminal Belawan. The research employed a descriptive quantitative method with a survey approach. The sampling technique used was stratified probability sampling, involving 67 permanent employees of PT Pelindo Multi Terminal Belawan as respondents. Data were collected through field observations and structured questionnaires, then analyzed using multiple linear regression with the assistance of SPSS version 15 software. The classical assumption tests indicated that the data met the required conditions for further analysis. The results of the study showed that the work environment has a positive and significant effect on employee performance (Sig. 0.000 < 0.05). Meanwhile, work motivation has a positive but not significant effect on performance (Sig. 0.072 > 0.05). Simultaneously, the F-test results proved that the work environment and work motivation together have a significant effect on employee performance (Sig. 0.000 < 0.05). The contribution of these two variables to employee performance was 46.8% (Adjusted R Square), while the remaining 53.2% was explained by other factors not included in this study. The conclusion of this research is that the work environment is a vital factor that must be maintained and improved by the company to ensure optimal employee performance. Although work motivation did not show a significant influence, it still requires improvement, particularly in aspects such as career development, recognition, and a fair reward–punishment system. These findings are expected to provide valuable input for the management of PT Pelindo Multi Terminal Belawan in formulating strategic policies to enhance sustainable employee performance.